Photini Constantopoulou (επιμ.), The Foundation of the Modern Greek State. Major Treaties and Conventions (1830-1947), Υπουργεΐο Εξωτερικών, Αθήνα 1999 - ΛΟΥΚΟΣ, ΧΡΗΣΤΟΣ (Μνήμων, 2002)
Δεν παρατίθεται περίληψη.